Framing Political Identity on Instagram: Personal Branding and Public Engagement in the 2024 Indonesian Presidential Election - Frizki Yulianti Nurnisya; Mohd Faizal Kasmani (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Non-Indexed Publication